Activation pattern of trunk, thigh and lower leg mucles during underwater dolphin kick in skilled female swimmers - Kobayashi, K.; Takagi, H.; Tsubakimoto, S.; Sengoku, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
This study investigated the muscle activation pattern between the agonist and the antagonist muscles in the trunk, thigh and lower leg during underwater dolphin kick. Thirteen female elite swimmers participated in this study and they performed 15 m underwater dolphin kick swimming at maximum effort. The surface electromyography (sEMG) of six muscles were measured and the muscle activation pattern between the agonist and antagonist muscles in the trunk, thigh and lower leg were estimated from the sEMG data. As results, the trunk and the thigh muscles showed a reciprocal activation pattern during one-kick cycle. However, the activation pattern of the lower leg muscles did not show a reciprocal pattern and it was clarified that the lower leg muscles were co-activated during the upward kick phase.